External mass transfer effect for immobilized penicillin amidase in recirculated packed bed reactor - 192062 Lim, Chia Ching; Hea, Khim Long; Mohamad Roji Sarmidi; Malaysian Science and Technology Congress (2000 : Kota Kinabalu, Sabah) (Skudai : Universiti Teknologi Malaysia, 2000)
50